Effect Of Leadership Style On The Behavior Employees With The Organization A Political Variable As Mediation (Studies On The Banks BRI In Madiun) - Ahmadi, Herman (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2013)
The aim this study is to analyze the effect of leadership style (transformational and transactional) on employee behavior (in-role and extra-role), which mediated a political organization. The sample is 120 employees of Bank BRI in Madiun, a random sampling technique based on stem number of employees. Data analysis using SEM with LISREL program. The results of this study indicate that 1) Transformational leadership style has positive influence on behavior in the role of employees, 2) Transformational leadership style has no effect on extra-role behavior (Organizational citizenship behavior, OCB), 3) Transactional leadership style did not affect employees' behavior in role , 4) Transactional leadership style has positive influence on OCB behaviors (extra-role) of employees, 5) Transformational leadership style has positive influence on employees 'political organization, 6) Transactional leadership style has positive influence on employees' political organization, 7) Political organization negatively affect the behavior in the role of employees, 8) Political organization negatively affect the behavior of OCB (extra-role) of employees, 9) Political organization to mediate the influence of transformational leadership behaviors in the role of employees, 10 Political organizations mediate the influence of transformational leadership on OCB behavior (extra-role) employees, 11) Political organization to mediate the effect of transactional leadership role behavior in employees, and 12) Political organization to mediate the influence of transformational leadership on OCB behaviors (extra-role) of employees at Bank BRI in Madiun.Keywords: Transformational leadership style, Transactional Leadership Style, Political Organization, in-role behavior, extra-role behavior, and OCB